Interpretation of Paired Verses with a Science Approach - Arif Iman Mauliddin (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2022)
The belief that the Qur'an contains all kinds of knowledge in the universe, including modern science, has inspired some interpreters to create an interpretation of the Qur'an with a scientific nuance. This paper aims to see how the interpretation of other sciences. This study uses a descriptive analysis method of books and journals that discuss paired verses. Whether we realize it or not, the verses in the Qur'an are very close to scientific studies. One of the things described in the Qur'an is that everything is created in pairs. This paper includes several verses and their interpretations that show that the study of the Qur'an is in line with scientific studies. So that the interpretation of this verse produces new studies.